WATER SOLUBILITY IN ALUMINOSILICATE MELTS - McMillan P.F.; Holloway J.R. (My University, 1987)
We have compiled water solubility data for a wide range of natural and synthetic aluminosilicate melts in a search for correlations between melt composition and solubility. The published data reveal some interesting systematics. For example, molar water solubility increases with decreasing silica content in binary and pseudobinary silicates, and much higher solubilities are associated with alkali systems compared to alkaline earth silicate melts. Water solubility increases regularly with decreasing silica content along the silica-nepheline join. From the limited data available for potassium and calcium aluminosilicate melts, these systems appear to behave differently to sodium aluminosilicates. The compiled data are not nearly extensive enough to begin to understand the effects of melt composition on solubility. We suggest that many more systematic studies for a wide range of aluminosilicate melts will be necessary before we can systematize and understand the compositional dependence of water solubility. We have also examined results of experiments designed to probe the details of the water dissolution mechanism, and discuss the present state of interpretation of these data. We conclude that although considerable progress has been made, the water dissolution process is still not well understood at the molecular level, and remains an important research problem.